Impulse Buying of Fashion Products by Xi Grade Social Studies Public High School Students in Semarang - Hidayah, Ari Fatihatul; Wahyudin, Agus; Muhsin, Muhsin (Journal of Economic Education, 2019)
Impulsive buying is a psychoemonic phenomenon that happened to many people's lives in urban areas, especially to teenagers. This is because teens are easily influenced by advertising, lacks frugal thinking, less realistic and impulsive. This study aims to analyze and identify impulse buying behavior of XI grade social major (IPS) public high school (SMA Negeri) students in Semarang. Shopping lifestyle, fashion involvement, hedonic shopping values, positive emoticons and self control are used to measure the impulse buying behavior in students. This study used a quantitative approach with a population of 719 students and the sample are 257 students. The number of samples was determined using the Slovin formula, the sampling technique used is probability sampling. Data collection techniques used is questionnaire. Data analysis used was descriptive analysis and moderation regression analysis. The result of moderation regression analysis shows that hedonic shopping value has a direct influence on impulse buying. But shopping lifestyle, fashion involvement and positive emotion do not directly affect impulse buying. Indirectly shopping lifetyle and hedonic shopping value affect impulse buying through self control, while fashion involvement and positive emotion indirectly do not affect impulse buying through self control.